A Study on How Psychological Capital, Social Capital, Workplace Wellbeing, and Employee Engagement Relate to Task Performance. (May 2022) - Al Kahtani, Nasser Saad; M. M., Sulphey
The current study was conducted to examine the relationship between Psychological capital (PsyCap), Social capital, Workplace wellbeing, and Employee engagement in Saudi Arabia. Only limited evidence exists about the relationship between the constructs in Saudi Arabia. Data was collected from 395 gainfully employed Saudi samples, using five standardized and validated questionnaires. The data was analyzed using Exploratory and Confirmatory Factor Analysis and Structural Equation Modeling (SEM). SEM was conducted using the R Program. The results indicate a significant positive relationship between PsyCap, workplace wellbeing, and employee engagement with task performance. No significant relationship was found between social capital and workplace wellbeing. By addressing a previously unexplored area, the present study has provided substantial contribution to the literature